1994
DOI: 10.1246/bcsj.67.3107
|View full text |Cite
|
Sign up to set email alerts
|

Surface Acidity-Cracking Activity Correlation in Chromium Pillared Clays

Abstract: Chromium pillared montmorillonite and vermiculite catalysts have been prepared by intercalation with hydrolyzed metal ion solution. Pillaring solutions with different chromium concentrations were prepared by varying the base to chromium ratio. The catalysts were characterized by nitrogen adsorption, XRD, and IR studies. The nature of the acid sites was characterized by means of IR spectra data on pyridine adsorbed chromium pillared catalysts. The acidity of the samples was determined by butylamine titration. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Several authors have reported that cracking and dehydrogenation activities may be related to the presence of Bro¨nsted and Lewis acid sites [35][36][37]. It is well known that the intercalation and pillaring of smectitic clays give rise to new acid sites, which provide the pillared solids with an additional acidity with respect to that of the starting clay [3].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported that cracking and dehydrogenation activities may be related to the presence of Bro¨nsted and Lewis acid sites [35][36][37]. It is well known that the intercalation and pillaring of smectitic clays give rise to new acid sites, which provide the pillared solids with an additional acidity with respect to that of the starting clay [3].…”
Section: Resultsmentioning
confidence: 99%
“…The function of solid acid in raw saponite can be improved by the insertion of ZrO 2 in the interlayer of clay structure by pillarization scheme. As reported in previous investigations, The enhancement of surface profile especially the acidty come from the ZrO 2 combination with clay was lineary correlated with the enhancement of its role in acid catalyzed reaction [3]- [5]. The present work focuses on the study of physicochemical parameters that affect Zr-PILS to catalyze the esterification of menthol.…”
Section: Introductionmentioning
confidence: 54%